The use of bacterial cellulose from kombucha to produce curcumin loaded Pickering emulsion with improved stability and antioxidant properties - Zhiyu Li; Wenxiu Hu; Jiajia Dong; Fidelis Azi; Xiao Xu; Chuanhai Tu; Sijie Tang; Mingsheng Dong (Food Science and Human Wellness, 2023)
Curcumin is a bioactive molecule with limited industrial application because of its instability and poor solubility in water. Herein, curcumin-loaded Pickering emulsion was produced using purified bacterial cellulose from fermented kombucha (KBC). The morphology, particle size, stability, rheological properties, and antioxidant activities of the curcumin-loaded Pickering emulsion were investigated. The fluorescence microscope and scanning electron microscopy images showed that the curcumin-loaded Pickering emulsion formed circular droplets with good encapsulation. The curcumin-load Pickering emulsion exhibited better stability under a wide range of temperatures, low pH, sunlight, and UV-365 nm than the free curcumin, indicating that the KBC after high-pressure homogenization improved the stability of the CPE. The encapsulated curcumin retained its antioxidant capacity and exhibited higher functional potential than the free curcumin. The study demonstrated that the KBC could be an excellent material for preparing a Pickering emulsion to improve curcumin stability and antioxidant activity.